Voltage Control via Tap-Changing Transformer Using the Holomorphic Embedding Load Flow Method Based on Total Multiplication of Polynomials - Glaucus R. S. Lima; Edimar J. Oliveira; Leonardo W. Oliveira (IEEE Access)
This paper presents an innovative strategy for voltage control in electric power systems by integrating tap-changing transformers with the Holomorphic Embedding Load Flow Method based on Total Multiplication of Polynomials (HELM/TMP). Using an alternating adjustment scheme, the proposed approach takes advantage of the superior numerical robustness and computational efficiency of the HELM/TMP over conventional power flow methods. The method is validated through extensive simulations performed on IEEE 14, 30, 57, and 118-bus test systems, including load variations and wind power. Representative wind generation scenarios produced by applying the modified Iterative Self-Organizing Data Analysis Technique Algorithm are used, considering annual historical generation data. The results show that the proposed technique maintains the voltage within the specified limits with an accuracy comparable to Newton-Raphson-based approaches while achieving an approximately 90% reduction in computation time. These case studies confirm the robustness, scalability, and real-time applicability of the proposed HELM/TMP-based voltage control. The main contribution lies in the use of HELM/TMP, which significantly accelerates the voltage control solution process, thus validating the applicability of the framework for real-time scenarios. This is particularly relevant for complex power systems, including those with critical loads, intermittent generators, and demanding operating conditions.